HEALTH LEVEL MONITORING THROUGH HEART RATE AND OXYGEN LEVEL DETECTION WITH ANDROID-BASED INTERNET OF THINGS - Wahjudi, Dody; Sudaryanto, Eko; Suprayitno, Tegar; Darmawan, Isra’ Nuur (Journal of Electronic and Electrical Power Applications, 2023)
One of the most important organs of the human body is the heart. The heart manages the circulation of oxygen-rich blood and transports food waste from the body. Heart rate can help diagnose heart problems and show how healthy the heart is. The aim of this research is to create a tool to monitor the work of the heart through heart rate and oxygen levels in the blood vessels to determine the level of heart health via the Internet of Things (IoT). The research method used was to create a prototype designed with IoT using the ESP32 Node MCU and the Blynk application via the MAX30100 sensor. Testing the sensor voltage obtained an average input voltage value of 4.14 V and an output voltage of 3.3 V. The average error value was 0.6 V and the percentage calculation was 79.7%. Monitoring tools to detect oxygen levels in blood vessels and successfully read data. The test results in table 3.3 were carried out with an average heart detection result of 82.6 BPM (Beat per Minute) and an oxygen level detection result of 95%. Monitoring can also be seen via the Blynk application on Android or other gadgets. The sensor reading results for oxygen levels are almost accurate, having the same reading value, while the heart rate measurement results are less variable according to physical conditions. Using the Blynk application is very easy to use both directly and remotely.